Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
x2+x+x2-2x+x-2=0
x2+x+x2-x-2=0
2x2-2=0
2(x2-1)=0
x2-1=0
x2=1 =>x=1 hoặc x=-1
2. y = cot g(x2 + 2x)
Ta có: ( cot gu)' = - \(\frac{u^'}{sin^2u}\)
y' = - \(\frac{\left(x^2+2x\right)}{sin^2\left(x^2+2x\right)}=-\frac{2.\left(x+1\right)}{sin^2\left(x^2+2x\right)}\)
4. y = (1 + tgx)3
y = 3.(1 + tgx)2 (1 + 1gx)' (tgx)' = 1 + tg2x
= 3.(1 + tgx)2 (1 + tg2x) (un) = n.un-1 .u'
5. y = \(\sqrt{1+3cos^2x}\)
\(y=\frac{\left(1+3cos^2x\right)}{2.\sqrt{1+3cos^2}x}=\frac{-3.2.sĩn.cosx}{2.\sqrt{1+3cos^2}x}=\frac{-3sinx.cosx}{\sqrt{1+3cos^2}x}\)
A (x ) = 5x2 - \(\frac{1}{2}.x\) + 8x4 -3x2 + 9
A(x) = ( 5x2 -3x2 ) -1/2.x + 8x4 +9
= 2x2 -1/2.x +8x4 +9
1+2+3+1=7 nha bạn.
Chúc bạn hok tốt nha.
1 x 2 = 2
2 x 2 = 4
3 x 2 =6
MAGICPENCIL
HÃY LUON :-)
K NHA
#)Trả lời :
1 x 2 = 2
2 x 2 = 4
3 x 2 = 6
#~Will~be~Pens~#